2011
DOI: 10.1007/s00122-011-1716-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of Arabidopsis thaliana lipid-related orthologous genes in Brassica napus

Abstract: Quantitative Trait Loci (QTL) for oil content has been previously analyzed in a SG-DH population from a cross between a Chinese cultivar and a European cultivar of Brassica napus. Eight QTL with additive and epistatic effects, and with environmental interactions were evaluated. Here we present an integrated linkage map of this population predominantly based on informative markers derived from Brassica sequences, including 249 orthologous A. thaliana genes, where nearly half (112) are acyl lipid metabolism rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 53 publications
7
77
1
1
Order By: Relevance
“…associated with oil content, distributed on A1 and A8 in the RIL population (Yan et al 2009b), and were regarded as the same loci for oil content (Delourme et al 2006;Qiu et al 2006;Zhao et al 2012;Chen et al 2013;Jiang et al 2014). Hence, the association mapping results were in good agreement with published QTL detected in other B. napus populations.…”
Section: Association Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…associated with oil content, distributed on A1 and A8 in the RIL population (Yan et al 2009b), and were regarded as the same loci for oil content (Delourme et al 2006;Qiu et al 2006;Zhao et al 2012;Chen et al 2013;Jiang et al 2014). Hence, the association mapping results were in good agreement with published QTL detected in other B. napus populations.…”
Section: Association Analysissupporting
confidence: 77%
“…These works showed that seed oil content is quantitative in nature and controlled by multiple genes termed quantitative trait loci (QTL), found in almost all the 19 linkage groups, and the trait is affected by environment (G )E) (Burns et al 2003;Zhao et al 2005Zhao et al , 2006Delourme et al 2006;Qiu et al 2006;Amar et al 2008;Yan et al 2009b;Chen et al 2010Chen et al , 2013Sun et al 2012). Moreover, a QTL associated with oil content located in the linkage group 1 (A1) near the public SSR markers BRAS041 or BRAS078 of B. napus has been frequently reported (Zhao et al 2005(Zhao et al , 2012Delourme et al 2006;Qiu et al 2006;Chen et al 2013;Jiang et al 2014), and we also found CB10369 and BRAS041 were mapped to the adjacent regions. Similarly, it should also be mentioned that one QTL for seed oil content was mapped to linkage group A8 in different crosses (Burns et al 2003;Delourme et al 2006;Qiu et al 2006;Amar et al 2008).…”
Section: Association Analysismentioning
confidence: 99%
“…The two parents (Yuye 87 and Zheyou 50) and six bulks were used for bulked segregant analysis (Michelmore et al 1991) to identify markers linked to the BnLL1 gene. Two hundred and four markers, covering all 19 linkage groups, were selected from B. napus genetic map (SG map) based on a doubledhaploid population derived from Sollux 9 Gaoyou (Zhao et al 2012), and screened in two parents and DNA bulks. The markers showing polymorphism between lobed-leaf bulks and entire-leaf bulks were confirmed in population A1.…”
Section: Identification Of Markers Linked To Bnll1mentioning
confidence: 99%
“…Recently, some studies have used parental lines with significant differences in oil content (>10%) (Sun et al 2012;Wang et al 2013), which was useful to detect QTL. These studies showed that QTL for oil content were distributed on 18 of 19 B. napus chromosomes, except chromosome C4 (Ecke et al 1995;Zhao et al 2005Zhao et al , 2006Zhao et al , 2008Zhao et al , 2012Delourme et al 2006;Qiu et al 2006;Sun et al 2012;Wang et al 2013;Jiang et al 2014). The number of QTL detected varied from three (Ecke et al 1995) to 27 (Chen et al 2010) and explained phenotypic variation ranging from 1.2% (Delourme et al 2006) to more than 20% (Chen et al 2010;Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made in quantitative trait loci (QTL) mapping for oil content in rapeseed (Ecke et al 1995;Burns et al 2003;Zhao et al 2005Zhao et al , 2006Zhao et al , 2008Zhao et al , 2012Delourme et al 2006;Qiu et al 2006;Sun et al 2012;Wang et al 2013;Jiang et al 2014) that shed light on dissecting the genetic mechanism of oil content and provide a theoretical basis to develop effective breeding methods. Most of this research has been carried out using doubled haploid (DH) populations, including DY ('Darmor-bzh' × 'Yudal') and RNSL ('Rapid' × 'NSL96/25') (Delourme et al 2006), TN ('Tapidor' × 'Ningyou7') (Qiu et al 2006;Jiang et al 2014), SG ('Sollux' × 'Gaoyou') (Zhao et al 2005(Zhao et al , 2006(Zhao et al , 2008(Zhao et al , 2012, Z5 ('ZY036' × '51070') (Sun et al 2012), and KN ('KenC-8' × 'N53-2') populations. Meanwhile, only a few studies based on recombinant inbred line (RIL) population ) and intervarietal subsets of substitution lines (Burns et al 2003) have been performed.…”
Section: Introductionmentioning
confidence: 99%